Experimental study on the phase transformation point of crushable and noncrushable soils. Issue 2 (17th February 2017) - Shahnazari, Habib; Rezvani, Reza; Tutunchian, Mohammad Amin
ABSTRACT: Two marine calcareous deposits as crushable soils and a siliceous sand as a noncrushable soil were used in this study to compare their monotonic response. Undrained monotonic triaxial tests were conducted on samples, which were prepared in different relative densities and consolidated under various confining pressures. The location of phase transformation point in undrained response of the sands in different initial conditions was evaluated. The effect of important parameters including relative density, confining pressure, particle shape, and particle breakage on phase transformation point was assessed. The input energy applied per unit volume of the soils was used to interpret the shearing response of crushable and noncrushable soils. The results showed that calcareous sands have more tendencies in contraction. Particle shape and breakage play a key role in engineering behavior of crushable soils.